Analysis of Body Posture of Rice Processing Warehouse Workers Using OWAS Method (Ovako Working Analysis System) - Topan Nopanto; Ade Astuti Widi Rahayu; Fathurohman Fathurohman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research assessed the body posture of rice processing workers using the Ovako Working Analysis System (OWAS) method to identify postures leading to high musculoskeletal disorder (MSD) risks. The study observed seven workers in a rice processing warehouse, where 60% of work postures were classified as high-risk (Action Code 4). These postures, frequently involving lifting heavy loads and prolonged bending, significantly contribute to the prevalence of MSD symptoms such as back, arm, and leg pain. Data collection included systematic observation and analysis categorized by OWAS Action Codes. Immediate corrective actions, including ergonomic adjustments and improved training, are essential to mitigate these risks. The findings emphasize the need for ergonomic interventions to enhance worker safety, reduce injury risks, and improve productivity. This research provides valuable insights into the ergonomic challenges in rice processing environments, underlining the importance of regular posture assessments and proactive measures to create safer workplaces.Keywords: Musculoskeletal, Ovako Working Analysis System, Work posture